2001
DOI: 10.1093/bja/86.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for massive hepatic haemangiomatosis causing restrictive lung disease

Abstract: A 34-yr-old man with hepatic haemangiomatosis presented for orthotopic liver transplantation. His massively distended abdomen caused thoracic compression and severe restrictive lung disease. Respiratory failure was the principal indication for transplantation. Increased airway pressures, pulmonary hypertension, systemic hypotension caused by aorto-caval compression, and blood loss, complicated the intra-operative anaesthetic management. Weaning from mechanical ventilation was impaired by acute and chronic meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A total of 18 studies were finally included in the present analysis, which recruited 19 patients, as shown in Table 1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The mean age of patients was 39.9±8.6 years.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 studies were finally included in the present analysis, which recruited 19 patients, as shown in Table 1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The mean age of patients was 39.9±8.6 years.…”
Section: Resultsmentioning
confidence: 99%
“…Those exceeding 10 cm are rare and often termed as giant haemangiomas, and can present with fibrosis, thrombosis, and calcifications. Multiple haemangiomas can be found in 10% of cases 7. In a review by Carlo et al , while classifying haemangiomas based on size, they concluded that surgery should be considered for massive haemangiomas only if they cause symptoms such as abdominal discomfort or haematological alterations 8.…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies have described liver transplantation as a viable treatment option for patients with hepatic hemangiomatosis complicated with painful hepatomegaly, liver failure, portal hypertension, or heart failure due to hyperdynamic flow [23][24][25][26][27][28][29]. In a recent systematic literature review by Bhardwaj et al (September 2022), two patients with DHH underwent living donor transplantation [29] and orthotopic liver transplantation [27], respectively, with good status after a follow-up period of at least 6 months [18].…”
Section: Rare Liver Transplants Indications 21 Hepatic Hemangiomatosismentioning
confidence: 99%